Predictive value of admission biomarkers for mortality and rehospitalization in hypertensive crisis - Emir Bećirović; Minela Bećirović; Amir Bećirović; Amina Džidić Krivić; Armin Šljivo; Kenana Ljuca; Lemana Buljubašić; Nadina Ljuca; Admir Abdić; Emir Begagić (Medicinski glasnik, 2026)
Aim: To identify predictors of all-cause mortality and 6-month rehospitalisation in patients with hypertensive crisis, focusing on inflammatory indices, metabolic markers measured at admission, and antihypertensive treatment profiles. Methods: This prospective observational study included 210 adult patients with hypertensive crisis. Demographic, clinical, and therapeutic data were collected, including data on comorbidities, antihypertensive drug use, and treatment adherence. Laboratory parameters obtained at admission included neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), pan-immune-inflammation value (PIV), homocysteine, and uric acid. Patients were followed for 12 months. Multivariate logistic regression and receiver operating characteristic (ROC) curve analyses were conducted to identify independent predictors. Results: Mortality occurred in 10.9% of patients, and 27.1% were rehospitalised within 6 months. Deceased patients exhibited significantly higher levels of PLR (p=0.0329), SII (p=0.0355), homocysteine (p=0.0488), and uric acid (p=0.021). In multivariate analysis, homocysteine (OR=3.55; p<0.001), uric acid (OR=1.03; p=0.007), PLR (OR=1.04; p=0.047), and SII (OR=1.01; p=0.030) remained independently associated with mortality. Chronic kidney disease (OR=2.15, p=0.012) and poor treatment adherence (OR=1.92; p=0.017) were also significant predictors. ROC analysis demonstrated moderate discriminative power, with AUC values of 0.68 for PLR, 0.66 for SII, 0.65 for homocysteine, and 0.63 for uric acid. Conclusion: Elevated inflammatory indices and metabolic markers, particularly homocysteine and uric acid, were independently associated with increased mortality risk. Additionally, chronic kidney disease and suboptimal adherence to antihypertensive therapy significantly contributed to adverse outcomes. These findings underscore the importance of comprehensive risk assessment and personalised management in this high-risk population.
Keywords: homocysteine; hypertensive crisis; inflammation; Medication Adherence; prognosis; uric acid